Using Administrative Health Data to Monitor Potential Adverse Health Effects in Environmental Studies - Scherer, K.; Kraut, A.; Yassi, A.; Wajda, A.; Bebchuk, J. (Environmental research, 1994)
Following episodes of environmental contamination, health professionals are limited in their ability to detect adverse health effects in surrounding communities due to lack of relevant baseline health data, resources, and appropriate control populations. The objective of this study was to ascertain the feasibility of using administrative health data for these purposes. The Manitoba Health Services Commission′s (MHSC) database is comprehensive since universal health care is free in Canada. As part of an evaluation of two proposed hazardous waste treatment sites, the feasibility of using MHSC′s data was tested by (a) defining the two study and control sites through use of MHSC′s population registry and (b) determining baseline morbidity rates through analysis of MHSC′s physician visit payment files; diagnoses were coded using ICD-9-CM. The results indicated that there were some differences between the groups studied in the age- and sex-standardized morbidity rates of diagnoses potentially influenced by exposures to chemicals. Use of administrative data provided by a national health service is an inexpensive and efficient way to create and follow potentially exposed cohorts residing in defined communities. Despite limitations related to small populations in exposed communities and lack of standardized diagnostic criteria by physicians, this method should be explored further in environmental studies.